Urnfield culture cemetery Sumerje near Gornja Bistrica (Črenšovci, North–Eastern Slovenia) - Tica, Gojko; Sagadin, Teja; Kumer Blaž; Bremec, Rok; Predan Primož (Arheološki vestnik, 2024)
This article presents the Sumerje cemetery near Gornja Bistrica, discovered during the construction of the Cirkovce–Pince power line. In an excavation area measuring 40 m × 40 m, 80 cremation graves were unearthed. An extensive monograph on the cemetery is currently in preparation, with some ongoing analyses; therefore only a few selected graves are fully presented, along with a typological classification of the finds and basic information about the cemetery. The cemetery can be dated to the late phases of the Urnfield culture, among the Ruše Urnfield group (stages Ha B1 to Ha B3 according to Müller-Karpe’s schema). Considering that the cemetery extends beyond the excavation field on all four sides, it is presumed to be a larger cemetery, comparable in size to other major Late Bronze Age cemeteries in Slovenia, such as Ruše, Pobrežje, Ljubljana, Dobova, and Obrežje.